The Role of General Beliefs, Emotions and Attitudes toward Controversial Advertising of FMCG Products in Vietnam - Pham, Quoc Trung; Do, Thuy Duong (Journal of Intelligent Communication, 2024)
The fast development of social media and online marketing brings a lot of benefits to business. In marketing, the use of controversial advertisements has increased in the last 2 decades. However, it is not clear whether consumers hold positive or negative attitudes toward controversial advertisements. Although the consumers’ attitudes toward competing brands are important determinants of their buying decisions, provocative messages could cause negative attitudes and negatively affect purchase decisions. While the issue of controversial or offensive advertising has been raised in Western countries, but there is a lack of study in this topic in developing countries like Vietnam. This study focuses on exploring the factors affecting to the attitude toward controversial advertising of consumers about FMCG products in Vietnam and suggesting solutions for applying controversial advertising in the Vietnamese context. Based on the related research, a research model is proposed including five variables: general beliefs, positive emotions, negative emotions, affective attitudes, cognitive attitudes. Through a survey of 286 valid samples, the research model has been tested using SEM/AMOS. The results show that all 6 hypotheses are supported. The research gives meaningful insights for any FMCG brand when it comes to deciding on controversial advertising strategy in Vietnamese market.